2019
DOI: 10.7197/cmj.vi.540726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravitreal injection into different quadrants on pain score

Abstract: To determine the effect of intravitreal injection into different quadrants on pain score and injection comfort. Method: 304 patients were divided into 8 groups that included 38 patients in each. The right and left eyes of the patients were divided into 4 quadrants, superior temporal, inferior temporal, superior nasal, and inferior nasal. Intravitreal injections were performed in the room only used for this purpose and by an experienced ophthalmologist. To eliminate drug-related factors only intravitreal ranibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…20 In a study conducted in the Central Anatolia Region of Turkey, 22.7% of the women stated that they had been exposed to violence by their husband's relatives and 19.7% of women stated that they had been exposed to violence by their own relatives. 26 When we compared our results to results of studies conducted in other countries, we observed that during the last one year, 7% of women in Ukraine have been exposed to physical violence and 6% have been exposed to verbal violence; 14.1% of women in Māori and 9.3% of women in the Pacific have been exposed to physical and/or sexual violence; 25.3% of women in rural areas of Nepal have been exposed physical violence and 46.2% have been exposed to sexual violence; 23.4% of women in the rural areas of Western Bengal have been exposed to domestic violence; 43.3% of women in Erbil, Iraqi Kurdistan region have been exposed to emotional violence, 15.2% have been exposed to physical violence and 12.1% have been exposed to sexual violence; 35% of women at the slums in Bengladesh and 20% of women at the non-slum areas have been exposed to physical violence; 28.3% of women in Nepal have been exposed to violence; 21% of women in China have been exposed to physical violence and 12% have been exposed to sexual violence. 24,[27][28][29][30][31][32][33] According to the result of studies conducted in Bangladesh, Brazil, Ethiopia, Japan, Namibia, Peru, Samoa, Serbia and Montenegro, Thailand, and the United Republic of Tanzania, women have been exposed to physical or sexual or both types of violence at varying rates between 4% and 54%.…”
Section: Prevalence Of Domestic Violence Against Women In Canakkale Amentioning
confidence: 99%
“…20 In a study conducted in the Central Anatolia Region of Turkey, 22.7% of the women stated that they had been exposed to violence by their husband's relatives and 19.7% of women stated that they had been exposed to violence by their own relatives. 26 When we compared our results to results of studies conducted in other countries, we observed that during the last one year, 7% of women in Ukraine have been exposed to physical violence and 6% have been exposed to verbal violence; 14.1% of women in Māori and 9.3% of women in the Pacific have been exposed to physical and/or sexual violence; 25.3% of women in rural areas of Nepal have been exposed physical violence and 46.2% have been exposed to sexual violence; 23.4% of women in the rural areas of Western Bengal have been exposed to domestic violence; 43.3% of women in Erbil, Iraqi Kurdistan region have been exposed to emotional violence, 15.2% have been exposed to physical violence and 12.1% have been exposed to sexual violence; 35% of women at the slums in Bengladesh and 20% of women at the non-slum areas have been exposed to physical violence; 28.3% of women in Nepal have been exposed to violence; 21% of women in China have been exposed to physical violence and 12% have been exposed to sexual violence. 24,[27][28][29][30][31][32][33] According to the result of studies conducted in Bangladesh, Brazil, Ethiopia, Japan, Namibia, Peru, Samoa, Serbia and Montenegro, Thailand, and the United Republic of Tanzania, women have been exposed to physical or sexual or both types of violence at varying rates between 4% and 54%.…”
Section: Prevalence Of Domestic Violence Against Women In Canakkale Amentioning
confidence: 99%
“…Comparison of Pain in Different Quadrants while giving Intravitreal Injection (18). In order for the drug to be 17 dispersed evenly throughout the eye, local most popular universal intraocular procedure .…”
Section: Resultsmentioning
confidence: 99%
“…One of these studies showed that prevalence of food allergy in the Turkish population seems to be low when compared with Northern and Western European countries [12]. Additionally it was reported that one of every 17 children had food allergy in Turkey [13]. Although food allergy is considered as a serious health problem, the data on the true prevalence of food allergy in the general population is inadequate [1] and many people, including food handlers are unaware that an allergic reaction to food could be lifethreatening [14].…”
Section: Introductionmentioning
confidence: 99%